Bent Femoral Nail Removal Technique: An Illustrative Case Report - T Revanth; Giriraj Harshavardhan (Journal of Orthopedics and Joint Surgery)
Long bone fractures are more commonly treated by intramedullary nailing for their advantages, such as minimal soft tissue damage, reduced blood loss, and early mobilization. Despite that it has some complications like infection, bleeding, neurovascular deficit, nonunion, malunion. One of the rare complications is in situ bending of nails. In such cases, the removal of the failed implant and re-stabilization of the fracture will be required. In the literature, several extraction techniques and algorithms are available for the removal of such implants. However, there is no specific protocol or guidelines for selecting a particular technique. It depends on the patient, surgeon, and availability of instruments.